Zinc Application Mitigates Copper Toxicity by Regulating Cu Uptake, Activity of Antioxidant Enzymes, and Improving Physiological Characteristics in Summer Squash - Farhad Behtash; Fatemeh Abedini; Hosein Ahmadi; Seyed Bahman Mosavi; Ahmad Aghaee; Mohammad Reza Morshedloo; Jose M. Lorenzo (MDPI AG, 2022)
Zinc (Zn) and copper (Cu) are essential micronutrients for the plant's growth, development, and metabolism, but in high concentrations, the elements disrupt normal metabolic processes. The present study investigated the effects of different concentrations (added to a Hogland-based solution) of zinc (control, 5, 10 mg L−1 ZnSO4) and copper (control, 0.1, 0.2 mg L−1 CuSO4) on the growth characteristics and biochemical indices of summer squash (Cucurbita pepo L.). Compared with control, a single application of Cu or Zn at both concentrations significantly declined fruit yield, growth traits, pigments content, and high content of these minerals and values of stress-related indices. Increased Cu concentration in the nutritional solutions reduced the activity of ascorbate peroxidase (APX) and guaiacol peroxidase (GPX). Copper at high concentrations intensified ROS production, aggravated oxidative stresses, and decreased the plant yield and productivity. Nonetheless, combining Cu and Zn could alleviate stress intensity by boosting antioxidant enzymes, redox regulation, and a resultant diminishment in the content of H2O2, proline, malondialdehyde, and minerals. The obtained results corroborate that the co-application of zinc in Cu-contaminated areas can improve the plant's economic yield and physiological parameters by hindering copper toxicity and enhancing the photosynthetic capacity.